Favoriser l’expression orale chez les apprenants universitaires grâce à des stratégies de communication (Revista de Divulgación Shimmering Words: Research and Pedagogy E-Journal, 2022)
Speaking in a foreign language can be a vast challenge for most learners, and this is the case of a group of learners in a university setting located in Cartagena. Therefore, this article reports the findings of a pedagogical intervention, which implemented communication strategies to foster university learners’ speaking skills. The strategies aimed to reduce learners’ reliance on their L1, to strengthen their L2 oral fluency, and to lower their affective filter when performing oral tasks. Twentytwo learners participated in the intervention stage, which consisted of six workshop that were designed including several communication strategies and then implemented. Data collected, in the action stage, displayed that communication strategies had a positive effect on learners’ L2 oral proficiency, and suggested that the implementation of these strategies and meaningful oral tasks were beneficial to broaden and to refine their lexicon, to improve their fluency, and to lower their affective filter.